2018
DOI: 10.1123/jab.2017-0124
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Walking Workstations on Biomechanical Performance

Abstract: Prolonged sitting has been associated with negative health effects. Walking workstations have become increasingly popular in the workplace. There is a lack of research on the biomechanical effect of walking workstations. This study analyzed whether walking while working alters normal gait patterns. A total of 9 participants completed 4 walking trials at 2.4 and 4.0 km·h: baseline walking condition, walking while performing a math task, a reading task, and a typing task. Biomechanical data were collected using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Although some studies suggested that work performance is not affected by walking concurrently [ 54 , 55 ], others, suggested the opposite [ 34 , 35 ]. These apparent contradictions most likely stem from differences in the type of tasks performed and their respective cognitive requirements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although some studies suggested that work performance is not affected by walking concurrently [ 54 , 55 ], others, suggested the opposite [ 34 , 35 ]. These apparent contradictions most likely stem from differences in the type of tasks performed and their respective cognitive requirements.…”
Section: Discussionmentioning
confidence: 99%
“…First, the number of participants was relatively small, which would limit generalization. However, the sample size was projected based on a previous study describing the effects of walking workstations on biomechanical performance in nine participants [ 35 ], and differences between the tested conditions were statistically significant. Second, nine out of the ten participants were under 28 years old, and all participants reported a healthy lifestyle (exercised at least twice a week); hence, results may be limited to similar populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a treadmill desk has shown limited effects on work performance and cognition in both chronic and acute interventions [11]. While studies have addressed the effect of different sitting positions on muscle activation and posture [12] and walking workstations on gait [13], limited research has examined biomechanical outcomes of interrupting sitting time. Miller and colleagues [14] reported walking and standing to elicit the same accumulated knee joint load, supporting the use of walking breaks due to greater energy expenditure over standing.…”
Section: Introductionmentioning
confidence: 99%